Assembly and budding of Ebolavirus. - Takeshi Noda; Hideki Ebihara; Yukiko Muramoto; Ken Fujii; Ayato Takada; Hiroshi Sagara; Jin Hyun Kim; Hiroshi Kida; Heinz Feldmann; Yoshihiro Kawaoka (PLoS Pathogens, 2006)
Ebolavirus is responsible for highly lethal hemorrhagic fever. Like all viruses, it must reproduce its various components and assemble them in cells in order to reproduce infectious virions and perpetuate itself. To generate infectious Ebolavirus, a viral genome-protein complex called the nucleocapsid (NC) must be produced and transported to the cell surface, incorporated into virions, and then released from cells. To further our understanding of the Ebolavirus life cycle, we expressed the various viral proteins in mammalian cells and examined them ultrastructurally and biochemically. Expression of nucleoprotein alone led to the formation of helical tubes, which likely serve as a core for the NC. The matrix protein VP40 was found to be critical for transport of NCs to the cell surface and for the incorporation of NCs into virions, where interaction between nucleoprotein and the matrix protein VP40 is likely essential for these processes. Examination of virus-infected cells revealed that virions containing NCs mainly emerge horizontally from the cell surface, whereas empty virions mainly bud vertically, suggesting that horizontal budding is the major mode of Ebolavirus budding. These data form a foundation for the identification and development of potential antiviral agents to combat the devastating disease caused by this virus.